Cationic η3-allyl sulfide complexes of nickel(II) for the polymerization of butadiene in aqueous emulsion - Padavattan, Govindaswamy; Jäkel, Christoph; Steinke, Tobias; Reimer, Valentine; Díaz-Valenzuela, Maria Belén; Crewdson, Patrick; Rominger, Frank (Journal of organometallic chemistry, 2010)
Reaction of the dimeric allyl-nickel(II) chloro complex [Ni(η3-C3H5)(μ-Cl)]2 (5) with sulfur donor ligands (L=L10-L13) in the presence of NaBAr4F (Ar4F=3,5-(CF3)2C6H3) gives the corresponding cationic mononuclear complexes of the type [Ni(η3-C3H5)(L)2]+ (1-4) [L=L10=diphenyl sulfide (1); L=L11=4,4′-thiodiphenol (2); L=L12=4,4′-thio-bis(6-tert-butyl-o-cresol) (3); L=L13=4,4′-thio-bis (6-tert-butyl-m-cresol) (4)]. All of these complexes were characterized by elemental analysis and NMR spectroscopy, as well as the representative complex 3 additionally by single-crystal X-ray analysis. In comparison to the known complex [Ni(η3-C3H5)(η6-BHT)][BAr4F] (BHT=3,5-di-tert-butyl-4-hydroxytoluene), the herein described cationic complexes show an increased stability towards water. The activity of the complexes for butadiene polymerization in aqueous emulsions was studied.
Im Text ist "3" hochgestellt
Online verfügbar 21 December 2009
Gesehen am 03.07.2023